2008
DOI: 10.1159/000120440
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Mesenchymal Stem Cells and Their Progeny to Medicines Used for the Treatment of Hematoproliferative Diseases

Abstract: Background/Aims: The influence of cytostatic medicines on mesenchymal stem cells (MSC) and their progeny, fibroblastic colony-forming units (CFU-F), was investigated. Methods: Mice were treated with busulfan, cyclophosphamide, cytarabine, methotrexate and bortezomib, as used in clinical practice. MSC and CFU-F were analyzed 3 days and 6 weeks after the treatment termination. To estimate MSC numbers, the ectopic foci formation method was used. Briefly, a donor bone marrow plug was transplanted under the renal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…MSCs have the expansion capacity, but the capacity is severely impaired in patients receiving high‐dose chemotherapy . The chemotherapy‐induced decrease in MSC expansion may result from a reduction of CFU‐forming frequency, a reduction in MSC proliferation, and an increase in MSC apoptosis . Our in vitro experiment demonstrated that CTX treatment damaged the typical morphology of MSCs and induced an impaired proliferation and an increased apoptosis in MSCs as evidenced by MTT and Annexin/PI assay, which are consistent with findings from other studies .…”
Section: Resultssupporting
confidence: 91%
“…MSCs have the expansion capacity, but the capacity is severely impaired in patients receiving high‐dose chemotherapy . The chemotherapy‐induced decrease in MSC expansion may result from a reduction of CFU‐forming frequency, a reduction in MSC proliferation, and an increase in MSC apoptosis . Our in vitro experiment demonstrated that CTX treatment damaged the typical morphology of MSCs and induced an impaired proliferation and an increased apoptosis in MSCs as evidenced by MTT and Annexin/PI assay, which are consistent with findings from other studies .…”
Section: Resultssupporting
confidence: 91%
“…It is worth noting that thanks to the low expression of HLA‐DR these cells may trigger a lower immune‐response, which was also confirmed by the absence of inflammatory areas in the recipients. For this reason we then decided to avoid the immunosuppressant drugs, to preclude interference in stem cell activity . In addition the low immune‐response and the reported absence of tumorigenesis justify in our experimental design the preclusion of a specific control group in healthy animals administrated with hAFS cells …”
Section: Discussionmentioning
confidence: 99%
“…To analyze the AFS cells in vivo potential, here we preferred to avoid the use of immunosuppressant drugs, as several controversial results have been recently reported regarding their influence on stem cells differentiation potential [61][62][63]. In this work a marked cellular response characterized by an infiltration of T-cells, NK cells and macrophages occurs in transplanted animals, independently from the presence or absence of the I/R injury.…”
Section: Discussionmentioning
confidence: 99%